Art In Japan since 1969 : Mono-Ha and Post Mono-Ha. (Tokyo : The Seibu Museum of Art, 1987)
Nobuo Sekine ; Lee U-Fan ; Kishio Suga ; Susumu Koshimizu ; Katsuro Yoshida ; Katsuhiko Narita ; Nobuo Yamanaka ; Yoshihisa Kitatsuji ; Kyoji Takubo ; Naoki Suwa ; Shigeo Toya ; Koichi Ebizuka ; Tadashi Kawamata ; Kenjiro Okazaki ; Mika Yoshizawa ; Mika Yoshizawa ; Kaoru Hirabayashi ; Hiroshi Kamo ; Takashi Fukui ; Michiko Yano ; Toshikatsu Endo ; Hirotake Kurokawa ; Shoko Maemoto
Art In Japan since 1969 : Mono-Ha and Post Mono-Ha, The Seibu Museum of Art, Tokyo, 26.06 - 19.07.1987
boek
Keywords: Japan